Spatial extension of the electromagnetic field from tightly focused ultra-short laser pulses. (March 2014) - Ionel, L.; Ursescu, D.
Abstract: It is shown that in the focus of ultra-short pulses of duration t, the equivalent relation s  =  ct, where c is the speed of light and s the spatial extent of the pulse of the collimated pulse, does not hold. While the duration of one pulse is constant and independent of the measurement point, the spatial extension of the ultra-short pulse can be spatially shorter a factor more than 10 compared to the one obtained from the usual relation. The result is explained in correspondence with the extension of the Rayleigh range. Few femtosecond long gamma bursts can thus be generated in Thomson backscattering experiments performed in the lambda cube regime.